IDENTIFIKASI MODEL FLUKTUASI INDEKS K HARIAN MENGGUNAKAN MODEL ARIMA (2.0.1) - - Habirun (Lembaga Penerbangan dan Antariksa Nasional, 2005)
The geomagnetic level called geomagnetic index. Based on the latitude, geomagnetic index for high to intermediate latitude is Kp index and for equator area is Dst index. For a certain location it is called local geomagnetic index, K index. Flunctuation of geomagnetic index is one of information that describes condition of space weather. Based on the above condition, this paper discusses identification of daily K index flunctuation model using Auto Regression Integrated Moving Average-ARIMA (2.0.1), 2, 0, and 1 order. Using observation data 1 order. Using observation data and reconstruction of four days data, it is found ARIMA (2.0.1) model 2, 0, and 1 order. Both model are validated, calculating errors and pattern correlation. Model validation result using observational data, showed the error of 2.18 and the pattern correlation of 0,99940. Model validation using reconstruction data, showed the error of 0.3582 and the pattern corelation of 0.9988.